Eksplorasi Peran Reactive Oxygen Species (ROS) yang diinduksi oleh Ekstrak Caesalpinia Sappan untuk Air yang Terkontaminasi Anabaena sp. - Mahendra, Himawan Akbar; Supraba, Intan; Kamulyan, Budi; Suyono, Eko Agus (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims toexplore the reduction of Anabaena sp. populations using Caesalpinia sappan extract, aiming to determine the optimal concentration to induce oxidative stress that weakens cell structures via increased production of Reactive Oxygen Species (ROS). Water quality parameterssuch as color, turbidity, and Total Dissolved Solids (TDS)were analyzed to evaluate the extract's effectiveness on the aquatic ecosystem. Employing a combination of the TRIZ (Theory of Inventive Problem Solving) method and a True Experimental design, the study optimized extract concentration variations and examined the ability of Caesalpinia sappan (sappan wood) to penetrate the peptidoglycan layer of Anabaena sp. Results obtained over two days indicate that the bioactive compounds in Caesalpinia sappan induce ROS, as evidenced by an increase in color intensity from day 1 to day 2 due to pigment release from Anabaena sp. in response to oxidative stress. Higher extract concentrations led to a significant reduction in Anabaena sp. populations, with the 100% concentration yielding an 86% decrease on day 2, alongside a color reading of 1209 Cu, turbidity of 39.6 NTU, and TDS of 114.5 mg/l. Microscopic observations revealed notable cell disintegration and damage in Anabaena sp. This study confirms that bioactive compounds, such as brazilin and flavonoids in Caesalpinia sappan, contribute to ROS generation, leading to cell death in Anabaena sp. via oxidative stress.